(untitled) (Scientific journal of the Fergana State University, 2026)
In this article, a scientific approach is taken to explain the essence and meaning of the concept of social justice. When analyzing justice from the point of view of social philosophy, it is necessary to distinguish between moral and social justice. In addition, Social Justice as a social philosophy problem includes two aspects: theoretical and practical. It is these two aspects that are covered in detail.